"Evaluación in vitrio de la actividad bacteriana de dos desinfectantes, sobre tres tipos de bacterias aisladas en el camal Municipal de Quevedo, 2019". - Urbina Dicao, Karen Solange (2020)
This research investigation was carried out in the Chemistry Laboratory, located in the Experimental Farm "La María" of the State Technical University of Quevedo, located at km 7 ½ of the Quevedo - El Empalme road, San Felipe Campus; Canton Mocache, Province of Los Ríos. Bacteria are unicellular microorganisms that reproduce by binary fission. Most are free-living, except for a few that are obligate intracellular, such as Chlamydias and Rickettsias. They have the energy-producing mechanisms and the genetic material necessary for their development and growth. Salmonella spp, is a bacterial genus belonging to the Enterobacteriaceae family consisting of facultative anaerobic intracellular gram-negative bacilli with peritrichous flagella that constitute an important group of pathogens for animals and humans.Listeria monocytogenes are short, regular, non-sporulated or branched gram-positive rods, which are usually observed in an individual arrangement or forming short chains. Escherichia coli belongs to a group of bacteria present in the intestine of humans and animals, the vast majority being harmless in them. However, there are some toxin-producing strains of E. coli called verotoxins or shiga-like toxins that can cause severe gastrointestinal conditions in humans. The Municipal Camal is a public entity, which is run and controlled by the Municipality of each canton, in this case, Quevedo city, and its primary mission is to serve the community, providing safe products. Keywords: Bacteria, slaughter, disinfectants, concentrations.